Distribution of envelope-specific and sarcoma-specific nucleotide sequences from different parents in the RNAs of avian tumor virus recombinants. - Wang, L H (1976)
The distribution of leukosis-virus- and sarcoma-virus-specific oligonucleotide sequences was investigated in the RNAs of viral recombinants selected for an envelope gene (env) from a leukosis parent and a sarcoma gene (src) from a sarcoma parent. For this purpose 20 to 30 RNase-T1-resistant oligonucleotides were chemically analyzed and mapped within the 10,000 nucleotides of each viral RNA relative to the 3'-poly(A) end. The resulting oligonucleotide maps were compared. Proceeding from the 3' to the 5' end, the maps of four recombinants contained: (i) in a segment of 2000 nucleotides, three to four src-specific oligonucleotides, so identified because they were shared only with the sarcoma parent; and (ii) in a segment of 8000 nucleotides, 20 oligonucleotides shared with the leukosis parent, of which six to seven were also shared with the sarcoma parent. Two other recombinants contained: (1) in a segment of 2000 (one) or 3000 (the other) nucleotides, three src-specific oligonucleotides; (ii) in a segment of 3000 (one) or 2000 (the other) nucleotides, five (one) or four (the other) oligonucleotides, all or some of which are env-specific, because they were shared with the leukosis parent; (iii) in a segment of 5000 nucleotides (both), 11 functionally unidentified sarcoma-virus-derived oligonucleotides, of which seven were also shared with the leukosis parent. The map locations of parental oligonucleotides were not changed in recombinants and all viral strains tested shared six to eight highly conserved oligonucleotides at equivalent map locations. The partial map -env-src-poly(A) emerged from the analyses of these recombinants.